Normotensive Primary Aldosteronism – Does it Exist? - Loh, Huai Heng; Norlela, Sukor (Georg Thieme Verlag KG, 2025)
Heightened aldosterone levels are associated with increased risk of renal sequelae, cardiovascular morbidity and mortality. Historically, primary aldosteronism is linked to hypertension. However, growing evidence reveals its presence even in normotensive individuals. This review consolidates data from diverse sources, delves into clinical studies of this underexplored condition, discusses the potential mechanisms, and provides a comprehensive and an up-to-date overview of the current state of knowledge. It highlights the evidence and understanding of normotensive primary aldosteronism, summarizes findings, and identifies opportunities for future research in this area. By addressing the clinical evidence, risk of hypertension development and possible mechanisms involved, this review aims to advance the understanding of this distinct form of primary aldosteronism and inspire further research in this emerging field.